﻿Bruneian teachers' attitudes towards push-in programme - Koay , Teng Leong; Siti Zaleha Hj Abdul Manaf (Universiti Kebangsaan Malaysia, 2010)

(untitled)
﻿This study examines the attitudes of Special Educational Needs Assistance (SENA) and regular teachers towards the push-in programme in Brunei Darussalam. The instrument used in this study was the Attitudes towards the Push-in Programme Scale (ATPIPS). The questionnaire consisted of 30 Likert items and eight open-ended questions. The 30 items in the ATPIPS were divided into six sub-scales: (I) support for the push-in programme, (2)social and academic needs of students with special needs, (3) barriers to the push-in programme, (4) benefits of the push-in programme to teachers (S) disadvantages of the push-in programme to students, and (6)teacher self-eficacy. In addition, semi-structured interviews of six teachers were conducted. The results show significant dtfferences in the attitudes towards the push-inprogramme between the SENA and regular teachers. The SENA teachers have had higher mean attitudes in the overall scale as well as in the six subscales of ATPIP than the regular teachers do. Finally, implications and recommendations for policy and practice, and future drrections for research are discussed